2022
DOI: 10.1049/cmu2.12414
|View full text |Cite
|
Sign up to set email alerts
|

Artificial noise aided directional modulation via reconfigurable intelligent surface: Secrecy guarantee in range domain

Abstract: Recently, the physical limitation of range-domain security guarantee for directional modulation with frequency diverse array was disclosed in Ding et al. (IEEE Access 8, 63302-63309 (2020)). Therefore, to recreate this significant secrecy realisation in both direction and range domain, the authors conceive an artificial noise aided directional modulation scheme via reconfigurable intelligent surface. Specifically, the angle of departure from the reconfigurable intelligent surface to co-direction receivers vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Optimization Problem (26) became a nonlinear fractional optimization problem. On the basis of the FP strategy in [43], we introduce parameter τ and transform Objective Function (28) as follows:…”
Section: Optimizing ψ Given V and φmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization Problem (26) became a nonlinear fractional optimization problem. On the basis of the FP strategy in [43], we introduce parameter τ and transform Objective Function (28) as follows:…”
Section: Optimizing ψ Given V and φmentioning
confidence: 99%
“…To investigate the effect of receiver beamforming on performance improvement on the basis of the system model of [26], the authors in [27] proposed two optimization algorithms to maximize the receiver power sum by jointly optimizing the PSM at IRS and receiver beamforming vectors at the user. In [28], aiming to maximize the SR of an IRS-assisted multiple-input single-output (MISO) DM network, the semi-definite relaxation method was utilized to derive the precoding and IRS PSM when the location information of an eavesdropper is available. Thanks to a combination with IRS, SR performance was significantly boosted.…”
Section: Introductionmentioning
confidence: 99%
“…1: Initialize feasible solutions β (0) , l (0) , v (0) , and Ψ (0) , calculate the secrecy rate R Given l (k) , v (k) , and Ψ (k) , solve (24) to yield β (k+1) .…”
Section: Algorithm 1 Proposed Max-sr-fp Algorithmmentioning
confidence: 99%
“…Based on the system model of [22], in [23], to enhance the SR performance, two low-complexity algorithms were proposed to jointly design the active and passive beamforming vectors of the IRS-assisted DM network. Moreover, a scenario in which Bob and Eve with the same direct-path and different reflectpath was considered in [24], and the genetic algorithm and alternating optimisation criterion were employed to solve the maximum SR non-convex problem when the Eve's location information was available. The above works showed that the passive IRS can boost the SR performance of the conventional DM network.…”
Section: Introductionmentioning
confidence: 99%
“…For maximizing the receive power sum of IRSassisted DM system, the authors in [27] proposed the general alternating optimization and zero-forcing methods to jointly design the PSM at IRS and receive beamforming vectors at user. In [28], aiming to maximize the security rate of IRSassisted multiple-input single-output (MISO) DM network, the semi-definite relaxation algorithm was utilized to derive the precoding and IRS PSM when the location information of the eavesdropper was available. Thanks to the combination with IRS, the security rate performance of them has been significantly boosted.…”
Section: Introductionmentioning
confidence: 99%